1984
DOI: 10.1002/art.1780271208
|View full text |Cite
|
Sign up to set email alerts
|

Clonally restricted anti‐igg antibodies in rheumatoid arthritis

Abstract: Clonally restricted anti-IgG antibodies were detected, by isoelectric focusing (IEF) and chromatofocusing techniques, in the sera of patients with rheumatoid arthritis (RA). Anti-Fab antibodies were predominantly acidic proteins with isoelectric points of 4.5-6.5 and displayed restricted spectrotype patterns. Proteins reactive with the Fc portion of IgG showed polyclonal spectrotype patterns with alkaline PI of 7.5-9.0. A limited array of anti-Fab spectrotypes was consistently detected in RA sera when analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1985
1985
1990
1990

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…1 b). These proteins, which we have previously identified as immunoglobulins (16), were most prominent in the acidic region of the gel, although diffuse uptake was often noted in the alkaline region. A comparison of the total protein pattern with the autoradiographs indicated that a high proportion of the proteins in the acidic region of the gel had anti-Fab properties (Fig.…”
Section: Methodsmentioning
confidence: 66%
See 2 more Smart Citations
“…1 b). These proteins, which we have previously identified as immunoglobulins (16), were most prominent in the acidic region of the gel, although diffuse uptake was often noted in the alkaline region. A comparison of the total protein pattern with the autoradiographs indicated that a high proportion of the proteins in the acidic region of the gel had anti-Fab properties (Fig.…”
Section: Methodsmentioning
confidence: 66%
“…Furthermore, treatment of sera with urea before analysis was obligatory for detection of the IgG4 subclass of antibodies, either by ELISA or by IEF (16 (14) have demonstrated that aFABA circulate with antikeyhole limpet hemocyanin antibodies after immunization of humans with keyhole limpet hemocyanin. Their studies might explain our finding higher IgG4 antidiphtheria antibody levels in untreated sera compared to those found in matched samples dialyzed against urea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These antibodies, particularly IgG RF, have been implicated in the pathogenesis of RA (Winchester, Agnello & Kunkel, 1970). However, a second group of anti-IgG antibodies, specific for Fab molecules, are also prevalent in RA (Persselin, Louie & Stevens, 1984;Persselin & Stevens, 1985; Abdou, 1985) and may also contribute to the disease process in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Since the RFs produced in adult RA are polyclonal in nature, although of restricted heterogeneity (17), most structural and serologic studies on RFs have taken advantage ofthe syndrome of mixed cryoglobulinemia. Extensive studies of these human monoclonal RFs have defined groups of RFs based on the expression of cross-reactive idiotypes (18,19).…”
Section: Introductionmentioning
confidence: 99%